2020
DOI: 10.2147/mder.s268057
|View full text |Cite
|
Sign up to set email alerts
|

<p>Auscultation System for Acquisition of Vascular Sounds – Towards Sound-Based Monitoring of the Carotid Artery</p>

Abstract: Introduction Atherosclerotic diseases of the carotid are a primary cause of cerebrovascular events such as stroke. For the diagnosis and monitoring angiography, ultrasound- or magnetic resonance-based imaging is used which requires costly hardware. In contrast, the auscultation of carotid sounds and screening for bruits – audible patterns related to turbulent blood flow – is a simple examination with comparably little technical demands. It can indicate atherosclerotic diseases and justify further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The main components of the acquisition system include the sensing hardware, a desktop application for real-time visualization of the acquired signals, a mechanical case to enclose the hardware, and a reliable skin-transducer interface to acquire high-quality signals. The device used for the audio acquisition was first introduced as an auscultation system for vascular sounds by Sühn et al [ 26 , 27 ]. To summarize, the device consisted of two Knowles digital microphones (Knowles Electronics LLC, SPH0645LM4HB, Itasca, Illinois, USA) assembled on a custom-designed printed circuit board and with a raspberry pi (Raspberry Pi Foundation, Raspberry Pi Zero W, Cambridge, United Kingdom) as a host system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main components of the acquisition system include the sensing hardware, a desktop application for real-time visualization of the acquired signals, a mechanical case to enclose the hardware, and a reliable skin-transducer interface to acquire high-quality signals. The device used for the audio acquisition was first introduced as an auscultation system for vascular sounds by Sühn et al [ 26 , 27 ]. To summarize, the device consisted of two Knowles digital microphones (Knowles Electronics LLC, SPH0645LM4HB, Itasca, Illinois, USA) assembled on a custom-designed printed circuit board and with a raspberry pi (Raspberry Pi Foundation, Raspberry Pi Zero W, Cambridge, United Kingdom) as a host system.…”
Section: Methodsmentioning
confidence: 99%
“…Both the host system and microphone were powered using a lithium potassium battery. As explained by Sühn et al, the two microphones were used to compare the differences in the signals when one was covered with an external membrane [ 27 ]. However, it was observed that there is no significant difference between the signals recorded by the two microphones.…”
Section: Methodsmentioning
confidence: 99%